The Relationship of The Role of Parents with The Children's Learning Discipline in Watugong Village, Alok Timur District - Dea, Magdalena; Fitriah, Fitriah; Solo, Yuliana Dua (Lembaga Riset Mutiara Akbar, 2022)
This study aims to determine the relationship between the role of parents and the discipline of learning children in Watugong Village, East Alok District. This research was conducted in Kloangkoja Hamlet, Watugong Village. This study uses descriptive qualitative research methods with data collection techniques used, namely interview techniques with the number of respondents studied with 60 people. Based on the results of interviews conducted by researchers with parents in Kloangkoja Hamlet, it is said that parents have educated, protect, serving, giving attention, providing children's learning facilities, and parents as well as a place to take out hearts, recognize children's learning difficulties, guide and encourage motivating children in learning discipline. Therefore, it can be concluded that the role of parents in relationships with children's discipline in Kloangkoja Hamlet can be said to be good.